Diseño, cálculo y construcción de un horno de lecho fluidizado alimentado con cascarilla de arroz para secado de arroz paddy (2020)
Alternative energy sources have been shown to be energy efficient and clean when compared to hydrocarbon-based ones. The waste produced by a certain industrial process can have a useful function such as the generation of clean energy. In this article, the design, calculation and manufacture of a fluidized bed furnace fed with rice husk to generate energy was developed, which will later be used in the rice production process. In this specific case, the energy produced was used to generate hot air, which is used in the drying process of the paddy rice, this allows reducing production costs and giving a better environmental direction to the rice husk.